(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article provides comprehensive support for the creative ideas and creativity of young people who are the successors of our future at a time of rapid development of our country on the path of innovative development, the formation of their knowledge, skills and advanced foreign experience. , improvement of the evaluation system on the basis of international criteria and requirements, study of international experience in this field, comprehensive comparative analysis of the existing system, close cooperation with relevant international and foreign organizations, research institutions, innovative study of materials science The analysis of teaching methods based on lim technologies is given